Manipulating Backward Propagation of Acoustic Waves by a Periodical Structure - 徐峥 钱梦騄 程茜 刘晓峻 (Chinese physics letters, 2016)
In the backward propagation of acoustic waves, the direction of phase velocity is anti-parallel to that of group velocity. We propose a scheme to manipulate the backward propagation using a periodicM structure. The dynamic backward propagation process is further experimentally observed. It is demonstrated that the oblique incident plane wave moves backward when it travels through the periodical structure and the backward shift can be controlled within a certain range.